Investasi Reksa Dana Syariah di Indonesia - Ahdiyat Agus Susilo (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2017)
The emergence of a mutual fund is a response to various questions concerning the investment, as well as the perfect solution for novice investors to invest their funds. With the capital that is not too big, and proficiency knowledge is limited, investors can narrow the risk of their investments, because of the diversification and management of collective funds, by institutional investment professionals. With the institution of mutual funds are expected to create a new perception that investing in the stock market is very easy and the necessary capital is not too large. In addition, the emergence of mutual fund institution is also a symbol that reinforce the perception that the capital market is not a container dominated and monopolized by investors who have big capital alone. Through mutual funds, lower middle strata of society can also participate to make investments and also to enjoy the promised benefits of the shares and other investment instruments.